A logic-based approach to compute a direct basis from implications - Cordero-Ortega, Pablo; Enciso-García-Oliveros, Manuel; Mora-Bonilla, Ángel; Ojeda-Aciego, Manuel; Rodríguez-Lorenzo, Estrella (My University, 2014)
Formal Concept Analysis is an emergent area in the topic of data analysis based on lattice theory. In this framework, a context is defined as the relation between a set of objects and a set of attributes and from here it is possible to extract relevant knowledge. One of the important topics is to study the implications between the attributes considered. In a context, some equivalent sets of implications can be compute using different techniques. We are studying the direct optimal basis, which enables us to compute the closure of a set of attributes in just one iteration. A Prolog method has been implemented that computes a direct basis from a set of implications.
Keywords: Retículos, Teoría de; Análisis de datos; Logic; Formal Concept Analysis; Implications; Basis